FLAGSHIP RELIGIOUS PROGRAM AT ISLAMIC COLLEGE: WHAT IS THE EFFECT ON STUDENTS' RELIGIOSITY? - Putri, Jihan Amelia; Sujadi, Eko; Putra, Eka (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
This study aimed to describe the religiosity of students engaged in religious programs compared to those who did not participate in such programs, followed by a comparative analysis of religiosity between these two groups. Utilized a comparative survey design, with 89 students from an Islamic university in Jambi Province, participating in the Religiosity among Muslims Scale through convenience sampling. Data analysis employed the Mann Whitney U Test. The research findings indicated that both students involved in religious programs and those not involved exhibited very high levels of religiosity. However, the average score of students in religious programs was higher than that of the other group. Additionally, hypothesis testing revealed no difference in the religiosity of students in both groups, suggesting no significant variations in religiosity aspects. This study hold important implications for campus-organized religious programs. It emphasized the need to maximize moral education programs in the Islamic Education curriculum, going beyond cognitive aspects. College leaders can develop and implement specialized programs, including enhancing the Islamic-based guidance and counseling services to enhance student religiosity levels. The findings indicated no disparity in the religiosity levels between students engaged in religious programs and those who are not. However, the group participating in specialized religious activities obtained a higher average score of 44.44 compared to non-participating group with an average score of 42.17. This underscored the significant role religious programs in bolstering religious knowledge, instilling moral values, and cultivating a more devout mindset.